CLINICAL AND PARACLINICAL FEATURES AND PATHOPHYSIOLOGICAL MECHANISMS OF DIGESTIVE SYSTEM DISORDERS IN PREMATURE INFANTS WITH PERINATAL PATHOLOGY - Ю. Годованець; T. Дроник (Bukovynian State Medical University, 2023)
Introduction. According to the World Health Organization (WHO), the incidence of preterm birth is 10-15%, or about 15 million newborns worldwide, and this number is increasing. The highest incidence of morbidity and mortality is observed in infants born before 32 weeks of gestation. Among other things, preterm infants have an immature digestive system, which leads to food intolerance. The formation of cumulative nutrient defi ciencies in the digestive system from birth puts children at risk of delayed psychophysical development and contributes to the development of negative long-term neurological consequences. Many of these complications have lifelong consequences for health, growth and development, both in infancy and later in life. Aim of the study. To improve the diagnosis of intestinal dysfunction in perinatal pathology in premature infants based on the study of risk factors and clinical and laboratory parameters. Materials and methods of the study. A comprehensive clinical and paraclinical examination of 91 premature infants with clinical manifestations of moderate and severe perinatal pathology with signs of disturbances of the functional state of the digestive system (group I, gestational age 29 (0/7) - 36 (6/7) weeks) and 57 conditionally healthy newborns (group II, gestational age 35 (0/7) - 36 (6/7) weeks) was performed. The total number of children studied was 148. Exclusion criteria were children with congenital malformations and septic conditions. The list of laboratory parameters used included: levels of α-1-antitrypsin (A1AT), PMN-elastase, albumin, fecal calprotectin (FC) and fecal elastase-1 (FE-1) in children's stool using enzyme- linked immunosorbent assay (ELISA), reagents from Immundiagnostic AG (Germany) on the basis of the German- Ukrainian laboratory "BUKINMED" (Chernivtsi, Ukraine). The scientifi c work was carried out on the basis of neonatology departments of the Chernivtsi City Clinical Maternity Hospital in 2014-2018. Informed consent of the parents of the child was obtained with adequate explanation of the purpose, objectives, methods and scope of laboratory and instrumental research methods. The study protocol was approved by the Biomedical Ethics Commission of the Bukovinian State Medical University, 2015. The studies were conducted in accordance with the basic provisions of GCP (1996), the Convention of the Council of Europe on Human Rights and Biomedicine (April 4, 1997), the World Medical Association Declaration of Helsinki on Ethical Principles for Research Involving Human Subjects (1964-2008), Order of the Ministry of Health of Ukraine ¹ 690 dated September 23, 2009 (as amended by Order of the Ministry of Health of Ukraine ¹ 523 dated July 12, 2012). Statistical processing of data was performed using the software "STATISTICA" (StatSoft Inc., USA, version 10), program MedCalc (https://www.medcalc. org/index.php). Comparison of quantitative indicators with normal distribution was performed using Student's t-test. The diff erence in parameters was considered statistically signifi cant at p<0.05. The thesis was carried out within the framework of the scientifi c topics of the Department of Pediatrics, Neonatology and Perinatal Medicine of the Bukovinian State Medical University: Research work on "Improvement of directions of prognosis, diagnosis and treatment of perinatal pathology in newborns and infants, optimization of schemes of catamnestic observation and rehabilitation" (State registration number 0115U002768, term of execution 01. 2015-12. 2019); Research work on "Chronobiological and adaptive aspects and features of autonomic regulation in pathological conditions in children of diff erent age groups" (State registration number 0122U002245, term of execution 01.2020-12.2024). Results and discussion. The studied laboratory parameters of stool in premature infants with signs of food intolerance in perinatal pathology revealed certain pathophysiological mechanisms of its development, including acute infl ammation, increased permeability of the intestinal mucosa, and exocrine insuffi ciency. Dysfunction of the digestive system is a consequence of complex autonomic and visceral dysfunction of the child's body against the background of hypoxia and morphological and functional immaturity at birth. An increase in the level of A1AT, PMN-elastase, albumin and a decrease in the concentration of FE-1 in feces are interdependent criteria of digestive system dysfunction. Increased permeability of the intestinal mucosa in conditions of local infl ammation leads to translocation of pathogenic and opportunistic microorganisms into the bloodstream, which probably exacerbates the clinical manifestations of endotoxemia in perinatal pathology of premature infants. The above justifi es the need to continue scientifi c research to develop a refi nement of comprehensive diagnosis and correction of digestive function in preterm infants. Conclusions. 1. Premature birth of children causes a high risk of adaptation disorders in newborns, which is due to the morphological and functional immaturity of the body and the realization of perinatal risk factors. 2. In the complex of vegetative- visceral dysfunction in conditions of perinatal pathology in newborns, there are signs of combined dysfunction of the digestive system, which is characterized by weakening or absence of sucking refl ex, regurgitation, intestinal stasis and paresis, delayed passage of meconium and transitional stools, fl atulence; in the most severe cases, persistent and prolonged decrease in tolerance to enteral nutrition is one of the characteristic manifestations of SIDS. 3. Increased levels of A1AT, PMN-elastase, albumin and decreased concentration of FE-1 in feces of children with nutritional dysfunction in the complex of signs of perinatal pathology are laboratory confi rmation of digestive system disorders in premature birth. 4. The pathophysiological mechanisms of transient disorders of the functional state of the digestive system, which cause clinical signs of food intolerance, are: acute infl ammation, increased permeability of the intestinal mucosa and exocrine insuffi ciency. Increased permeability of the intestinal mucosal barrier leads to increased translocation of pathogenic and opportunistic microorganisms into the bloodstream, which contributes to the growth of endotoxemia in perinatal pathology of premature infants. 5. Harmonization of clinical and paraclinical criteria for disorders of the functional state of the digestive tract in the complex of perinatal pathology will increase the eff ectiveness of diagnostic measures in the neonatal period, especially in premature infants, and improve approaches to medical care by improving the range of diagnostic and therapeutic measures.